Hematopoietic stem cell transplantation of an adolescent with neurological manifestations of homozygous missense PRF1 mutation. Issue 12 (11th August 2014) - Hussein, Ayad Ahmed; Hamadah, Tuka; Qandeel, Monther; Sughayer, Maher; Amarin, Rula; Mansour, Asem; Chiang, Samuel C.; Al‐Zaben, Abdulhadi; Meeths, Marie; Bryceson, Yenan T.
Abstract Individuals with biallelic truncating PRF1 mutations typically present with fulminant early‐onset familial hemophagocytic lymphohistiocytosis (FHL). We report a 19‐year‐old male with a 5‐year history of recurrent fever and headaches progressing to refractory seizures. Brain imaging revealed multiple ring enhancing lesions. Laboratory investigations demonstrated that the patient displayed defective lymphocyte cytotoxicity and carried a homozygous missense PRF1 mutation, c.394G > A (p.Gly132Arg). The patient was successfully treated with chemo‐immunotherapy followed by matched related allogeneic hematopoietic stem cell transplantation (HSCT). Our findings demonstrate that prompt HSCT of late‐onset FHL with primarily neurological manifestation can reverse central nervous system symptoms and improve long‐term outcome. Pediatr Blood Cancer 2014;61:2313–2315. © 2014 Wiley Periodicals, Inc.